We'd rather hire Guðmund and Anna than Muhammed and Aisha? The impact of a Muslim name on resumes - Kristinsson, Kári; Sigurðardóttir, Margrét Sigrún (School of Social Sciences, 2023)
Both Icelandic and international studies indicate that particularly high prejudice is observed against people with a Muslim background. As a result, the focus of this article is on prejudice against Muslim immigrants in Iceland. Job description and four curriculum vitae were set up and the general public was asked to evaluate randomly one applicant. Applicants were all the same, but names (Icelandic reference, Muslim reference) and gender (male, female) were different. Results indicate that there are significant prejudices against individuals with Muslim names. Despite the fact that our methodology leadsto underestimation of prejudices, we find significant prejudices against Muslims. For comparison we find that the wage difference caused by a Muslim background are considerably larger than the gender pay gap in Iceland. In line with prior literature, prejudices seem to be larger towards female than to male Muslim job seekers. Bæði innlendar og erlendar rannsóknir benda til þess að sérstaklega mikilla fordóma gæti gagnvart einstaklingum með múslímskan bakgrunn. Í þessari rannsókn ákveðið að skoða fordóma gagnvart múslímskum innflytjendum á Íslandi. Starfslýsing og fjórar ferilskrár voru settar upp og var almenningur beðinn að meta einn umsækjenda af handahófi. Umsækjendur voru eins að öllu leyti öðru en því að nöfn (íslensk tilvísun, múslímsk tilvísun) og kyn (kona, karl) voru mismunandi. Niðurstöður benda til þess að töluverðir fordómar séu til staðar gagnvart einstaklingum með nöfn sem gefa til kynna að þeir séu múslímar. Þrátt fyrir að eiginleikar aðferðafræðinnar leiði til vanmats á fordómum teljast þeir töluverðir. Launamunur, sem myndast vegna múslímsks bakgrunns, er til dæmis töluvert meiri en launamunur kynjanna á Íslandi. Í samræmi við erlendar rannsóknir virðast þeir fordómar vera meiri gagnvart kvenkyns heldur en karlkyns múslímskum umsækjendum.